2013
DOI: 10.1111/pme.12154
|View full text |Cite
|
Sign up to set email alerts
|

Are Older Adults with Chronic Musculoskeletal Pain Less Active than Older Adults Without Pain? A Systematic Review and Meta-Analysis

Abstract: Objective. To compare the overall levels of physical activity of older adults with chronic musculoskeletal pain and asymptomatic controls.Review Methods. A systematic review of the literature was conducted using a Cochrane methodology and reported in accordance with the Preferred Reporting Items for Systematic Reviews and MetaAnalyses statement. Major electronic databases were searched from inception until December 2012, including the Cochrane Library, CINAHL, EBSCO, EMBASE, Medline, PubMed, PsycINFO, and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
121
2
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 147 publications
(142 citation statements)
references
References 67 publications
(206 reference statements)
8
121
2
5
Order By: Relevance
“…This result is in line with earlier studies showing that musculoskeletal pain is among the major reasons for low physical activity in older populations (Ashe et al 2009, Stubbs et al 2013. In the present study, the participants with internal fixation reported more pain and perceived more walking difficulties than patients with hemiarthroplasty or total hip replacement (I).…”
Section: Mobility Recovery After Hip Fracturesupporting
confidence: 82%
“…This result is in line with earlier studies showing that musculoskeletal pain is among the major reasons for low physical activity in older populations (Ashe et al 2009, Stubbs et al 2013. In the present study, the participants with internal fixation reported more pain and perceived more walking difficulties than patients with hemiarthroplasty or total hip replacement (I).…”
Section: Mobility Recovery After Hip Fracturesupporting
confidence: 82%
“…More importantly, it does not provide information about actual/observed physical functioning concerning mobility, agility or strength to accomplish physical tasks. Indeed, perceived physical functioning might be poorly linked to real activity levels (Stubbs et al, 2013). In future research, physical functioning should also be assessed using observational measures.…”
Section: Limitations Implications and Directions For Future Researchmentioning
confidence: 99%
“…Indeed, the prevalence of chronic pain is known to increase with age (e.g., Blyth et al, 2001;Johannes et al, 2010) and musculoskeletal chronic pain (in muscles, ligaments, tendons and/or bones) is one of the most prevalent pain conditions among older adults (e.g., Miranda et al, 2012). Furthermore, in this particular age group, chronic pain is often associated with depression, sleep disturbances, avoidance of social interactions and decreased physical activity (e.g., Lee, et al, 2015;Mort & Philip, 2014;Stubbs et al, 2013;Zimmerman, et al, 2015). Also, chronic (musculoskeletal) pain often strongly interferes with older adults' performance of their daily activities (Helme & Gibson, 1997;Mobily et al, 1994;Reyes-Gibby et al, 2002;Thomas et al, 2004); in other words, it is often associated with high levels of pain-related disability (e.g., Cleeland, 2009;Tait, et al, 1990).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…O fortalecimento musculoesquelético por meio da AF expressa-se através da melhoria da DMO, do conteúdo mineral ósseo, da mudança no estilo de vida (autonomia e independência) mesmo reconhecendo o impacto das enfermidades que o acompanham (STUBBS et al, 2013). No caso da DMO que está em constante perda com o avanço da idade, estudos mostram que a AF aumenta de forma gradual e lenta a DMO durante a adolescência e isso repercute na qualidade da saúde óssea na idade adulta (TINETTI, 2003;STUBBS et al, 2013).…”
Section: Fortalecimento Musculoesqueléticounclassified